A avaliação formativa no ensino de física: concepções para uma prática docente transformadora - Dutra, Luciana de Morais (2019)
The role of learning evaluation in Physics teaching is a complex subject that demands a conception of teaching practice that understands evaluation as a process and not as a product. In this sense, this research intends to reflect on the teaching practice and the teaching of Physics from a differentiated proposal of evaluation of the learning using, among some methodologies, an methodology of active evaluation online with the use of the Google Forms® tool from a point of view. The tool in question makes it possible to develop discursive questionnaires and / or accessible objectives through any device that has access to the Internet, as a learning evaluation resource, done in an unconventional way and privileging autonomy and responsibility, as well as setting up a form of encourage them to move beyond the boundaries of the classroom. In order to carry out the qualitative research, we follow the classes of seven high school classes, our research subjects, of a public school in the state of Rio de Janeiro that only works at night time and is located in the Maré Complex, in Bonsucesso, Rio de Janeiro. The classes were based on the contents proposed by the Minimum Curriculum adopted by the schools of the state public network of Rio de Janeiro and were elaborated from the perspective that the students are protagonists of the process of building their own knowledge. The activities were developed during a school year and the evaluation process was continuous with the dialogue in the classes, application of questionnaires to raise previous conceptions about the topics covered, research proposals, active online evaluation and the discussion in class of the results of this evaluation. Thus, for data collection, we use the questionnaires available in the Google® environment and a field notebook. Data analysis was performed through Content Analysis. As results, we point out that changes in the learning assessment process can only be achieved when conceptions about practice are also altered. It is understood that evaluating learning is also a way to enable students to learn to build their knowledge of Physics in an autonomous and contemporary way.